Unstable expansion of the CAG trinucleotide repeat in MAB21L1: report of a second pedigree and effect on protein expression. Issue 1 (1st January 1999) - Margolis, Russell L; Stine, O Colin; Ward, Christopher M; Franz, Mary L; Rosenblatt, Adam; Callahan, Colleen; Sherr, Meeia; Ross, Christopher A; Potter, Nicholas T
Abstract : MAB21L1, originally termed CAGR1, is the human homologue of the C elegans cell fate determining gene mab21 . MAB21L1, mapped to 13q13, contains a highly polymorphic 5′ untranslated CAG repeat that normally ranges from six to 31 triplets in length. A pedigree has been previously reported in which the repeat length is expanded to 45-50 triplets and is transmitted unstably between generations; the expansion did not correlate to a clinical phenotype but did exhibit somatic mosaicism. We now report a second pedigree with an expanded and unstably transmitted MAB21L1 CAG repeat of similar length. The expansion is not clearly associated with a clinical phenotype, though the complexity of the pedigree renders any conclusion concerning phenotype-genotype relationships speculative. The expansion did not result in decreased expression of MAB21L1 protein. The length, C-G rich composition, somatic mosaicism, and unstable transmission of the expanded CAG repeat in MAB21L1 resemble the premutations observed in other genes, such as FMR1 and MDPK, in which longer expanded repeats are associated with a clinical phenotype. This raises the possibility that longer expansions in the MAB21L1 repeat may also be associated with a clinical phenotype.